In situ POM and FTIR investigation on quiescent phase transition of polybutene‐1 from form II to form I. Issue 1 (6th January 2020) - Li, Xiangyang; Ding, Jianjun; Zheng, Kang; Chen, Lin; Tian, Xingyou
Abstract: Despite extensive investigations in the past decade, the factors affecting the phase transition of polybutene‐1 (PB‐1) form tetragonal form II to hexagonal form I were not clarified completely. In this study, quiescent phase transitions of PB‐1 within different morphological of crystals at different temperatures were investigated employing polarized optical microscopy and Fourier transform infrared spectroscopy. Results indicate that the phase transition depends not only on intercrystalline links but also on the lamellar thickness. The phase transition always occurs spontaneously first in thick form II lamellae. The intercrystalline links have opposite effects in the early and later stages. In the early stage, it can promote form I nucleation in some form II clusters, where these clusters were subjected to inward tensions of intercrystalline links. While in the later stage, it retards form I growth since subjecting to outward tensions of intercrystalline links. This study helps to identify more effective method to accelerate forms II‐I phase transition. Abstract : Form II to form I phase transition of polybutene‐1 was influenced by lamellar thickness and intercrystalline links simultaneously. The thicker the lamellar thickness, the easier the phase transition. The intercrystalline links have two opposite effects: accelerating form I nucleation in the early stage and retarding phase transition in the later stage. The role of intercrystalline links is to overcome resistance from fast dynamics of ethyl groups.